English The Influence of Debt Restructuring, Previous Year’s Audit Opinion, Leverage, Liquidity, Company Age, And Audit Lag on Going Concern Opinion : English - Adella Kerriza Cahyani; Ni Nyoman Alit Triani (Universitas Islam Lamongan, 2023)
Going concern opinion is the auditor's opinion in considering the ability of a company's business continuity. The aim of this research to analyze the effect of debt restructuring, previous year’s audit opinion, leverage, liquidity, company age, and audit lag on going concern audit opinion on trade, service, and investment companies listed on the Indonesia Stock Exchange (IDX) in 2019-2020. The number of trade, service, and investment companies sampled in this research was 109 companies with total sample was 218 samples. The analytical techniques used in this study include Descriptive Statistical Analysis, Model Feasibility Test, Overall Model Feasibility Test, Coefficient of Determination Test, and Hypothesis Testing using Logistic Regression Analysis with SPSS 25. This study shows that debt restructuring and previous year’s audit opinion has a positive effect, liquidity has a negative effect, while leverage, company age, and audit lag do not affect going concern audit opinion.